EFL Student-Generated Symbolism towards “God Sees the Truth but Waits” - Dwiana, Nadya; Indawan , Syahri; Anggraini, Dita Rizki (Universitas Dian Nuswantoro, 2025)
This study investigates EFL learners’ student-generated symbolism in responding to the short story “God Sees the Truth but Waits” by Leo Tolstoy. Employing a qualitative descriptive design, the participants were 20 sixth-semester students enrolled in a Literary Appreciation course in an English Education study program. After guided classroom discussions on symbolism as a reader-response strategy, the students were asked to create their own symbolic representations of the text and provide written explanations of their interpretations. The data, consisting of students’ symbolism and written responses, were analyzed thematically. The findings showed that student-generated symbolism enabled learners to engage in personal, critical, and multimodal meaning-making, revealing higher-order interpretive thinking in response to the literary text. The study suggests that student-generated symbolism may function effectively as a multimodal reader response that can be meaningfully integrated into EFL literature classes.